Successful hog marketing groups - Mintert, J.; Tynon, R.; Tokach, Michael D.; Langemeier, Michael R.; Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Ten hog marketing groups located in Kansas and Iowa were surveyed during 1993 to determine the success, operation, and management of hog marketing groups. Results offer insights into the structure and organization of cooperative hog marketing efforts. Several guidelines for organizing successful hog marketing groups are proposed. Producers interested in forming a marketing group should consider having a written agreement, hiring a marketing group coordinator, and marketing hogs on a carcass merit basis.
Keywords: Swine; Hog marketing groups